GROWTH AND CHARACTER VARIATIONS OF L-ALANINE POTASSIUM CHLORIDE SINGLE CRYSTALS - Dr. SEETHALAKSHMI K.; Dr. SURAPANENI KRISHNA MOHAN (International Journal of Pharma and Bio Sciences, 2016)
The emerging trend of Organic crystals with Non- Linear optical properties consistently increases the interest of researchers in the field of Crystal growth. The fast development of optoelectronic field imposes new and efficient nonlinear optical (NLO) materials for second harmonic generation in optical communication and optical data storage etc. A great deal of effort was put in the development of nonlinear optical (NLO) materials for second harmonic generation (SHG). Single crystals of L-Alanine doped with Potassium Chloride semi- organic crystals were grown by a Slow evaporation method in the ratio 1:0.25, 1:0.5, 1:0.75 , and 1:1. The identities of the crystals were confirmed by Single crystal X-Ray diffraction studies, Powder crystal diffraction studies . The mode of vibration of different molecular groups present in L- Alanine Potassium chloride were studied by FTIR and UV- Vis spectral analysis . Its NLO efficiency is estimated by Kurtz and Perry powder technique.